2018
DOI: 10.1177/1054773818791096
|View full text |Cite
|
Sign up to set email alerts
|

Living With Rheumatoid Arthritis in Spain: A Qualitative Study of Patient Experience and the Role of Health Professionals

Abstract: The aim of this study was to explore the experience of Spanish people living with rheumatoid arthritis (RA) and the support these people received from health professionals, particularly nurses. Nineteen patients with >1 year diagnosis, disease activity moderate or severe (DAS28 > 3.2), and already treated with disease-modifying antirheumatic drugs (DMARDs) were interviewed. A thematic analysis was performed to interpret the discourses. The difficulties of symptom management; the need for home-adaptations, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…From a meta-synthesis of 32 studies, we identified six conceptual domains in which the self-management of RA was experienced: (a) of managing life with RA. [31][32][33][34]37,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] This involved accepting the pain associated with the condition, recognizing one's limitations and adapting one's behaviour accordingly. Social comparison was a common strategy across the studies.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…From a meta-synthesis of 32 studies, we identified six conceptual domains in which the self-management of RA was experienced: (a) of managing life with RA. [31][32][33][34]37,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] This involved accepting the pain associated with the condition, recognizing one's limitations and adapting one's behaviour accordingly. Social comparison was a common strategy across the studies.…”
Section: Synthesismentioning
confidence: 99%
“…Social comparison was a common strategy across the studies. 30,32,34,41,[44][45][46]48,49,51,53,[55][56][57][58][59] Downward comparisons were used to compare oneself to someone in a worse situation or condition: 57(p282) .…”
Section: Synthesismentioning
confidence: 99%
“…Previous research has demonstrated a correlation between depression and the patient’s concerns about her/his appearance when living with RA, which is something that should be routinely assessed. 54 Another study with patients with established RA addresses the difficulties of living with a deteriorating self-image and problems finding clothes and shoes due to deformities, 55 which differs from concerns among the patients in the present study about physical appearance early in the disease. The treatment of early RA has been more aggressive during the last decade with better long-term treatment outcomes thus generating differing patient preferences from those previously held, which highlights the significance of the study’s result.…”
Section: Discussionmentioning
confidence: 79%
“…[15][16][17] A number of studies across the globe report patients' perceptions and experiences of onset of symptoms, seeking medical help and self-management strategies. 18,19 Most of these studies emerge from Western countries where public health systems are well organized for NCDs and are distinct from those in India. Literature shows that inherited cultural beliefs impacting upon seeking medical help can be similar among the migrated population to other countries.…”
Section: Introductionmentioning
confidence: 99%
“…For example the UK rheumatology research in ethnicity has documented comparable cultural illness beliefs impacting on delay. 20 However, data on seeking medical advice in India are lacking and therefore this study was set up to explore the perceptions of participants with RA living in India. Data from this study was used to investigate the impact of RA on work productivity which is published elsewhere.…”
Section: Introductionmentioning
confidence: 99%